Research on the Role of Computer Image Technology in Visual Communication Design. Issue 3 (August 2021) - Fu, Lin
Abstract: Computer image came into being at the end of 1980s, and it has experienced more than 30 years of development. Image processing technology has been widely used and has become modern applied science. Computer technology is playing an increasingly important role in people's daily life. The use of computer technology is becoming more and more extensive along with the construction and development of information society nowadays. People's daily life and work are inseparable. Computer graphics has also been fully valued, which greatly improves the overall effect and level of visual communication design. Graphic image processing technology is also widely used in today's society, the works designed with it can bring great impact on people's vision. This paper analyzes the meaning of computer graphics and image technology and visual communication design, and on this basis, expounds the significance of computer graphics and image technology on the realization of visual communication design elements, hoping that the results can bring some help to the relevant leading city [1].